The Adoption of Digital Marketing by MSMEs Selling Halal Products: Opportunities and Challenges - Suleiman, Abdullahi Muhammad; Adamu, Alhahi Ibrahim Baba; Adamu, Sadiq Ibrahim (Malacca: Journal of Management and Business Development, 2025)
The digital economy's rapid growth is reshaping global business practices, presenting unique opportunities and challenges for Micro, Small, and Medium Enterprises (MSMEs). In Muslim-majority countries like Indonesia and Nigeria, halal-based MSMEs are crucial to economic development. This study investigates the adoption of digital marketing tools—such as social media, e-commerce platforms, and electronic payment systems—by these businesses. It explores how digitalization can enhance competitiveness while promoting Islamic ethical values like transparency, fairness (‘adl), and trust (amanah). The research identifies key challenges hindering adoption, including limited digital literacy, resource constraints, and infrastructural gaps. Conversely, it highlights the significant opportunities for market expansion, consumer trust-building, and inclusive economic growth that effective digital integration offers. By bridging Islamic economics with digital era realities, this study provides valuable insights for policymakers, educators, and entrepreneurs aiming to empower halal MSMEs in a rapidly evolving global marketplace.